Sylo - MacHale, D. J. (Razorbill, 2013)
When a secret branch of the U.S. Navy known as SYLO quarantines Pemberwick Island, Maine, claiming it has been struck by a deadly virus, high schooler Tucker is wrapped up in the ensuing chaos. Knowing there is more to the story, Tucker investigates and uncovers clues that could reveal the truth behind this perplexing mystery.